Contribution of mesothelial cells in the expression of inflammatory-related factors in omental adipose tissue of obese subjects - Darimont, C; Avanti, O; Blancher, F; Wagniere, S; Mansourian, R; Zbinden, I; Leone-Vautravers, P; Fuerholz, A; Giusti, V; Mace, K (International Journal of Obesity, 2008)
Objective: The objective of this study was to determine the contribution of mesothelial cells, present in human omental adipose tissue (OAT) but not in the subcutaneous depot (SAT), on the expression of inflammation-related factors. Design: Comparison of the expression profiles of inflammation-related genes in mesothelial cells with those in the adipocyte-enriched (AEF) and stromal vascular fractions (SVF) and localization of interleukin-18 (IL-18) expression in adipose depots. Subjects: Eleven obese Caucasian female subjects undergoing gastric bypass surgery (body mass index: 43.6±1.3 kg/m 2 ; age: 41.6±2.3 years). Measurements: The expression profiles of cytokine and chemokine-related genes in mesothelial cells and in cell fractions prepared from OAT were assessed by the microarray technique. The differential expression of IL-18 was confirmed by real-time PCR and the protein was localized in adipose depots by immunohistochemistry. Results: Microarray data analysis demonstrated that, of the 16 cytokine and chemokine-related genes that were upregulated in mesothelial cells compared with the AEF, IL-18 was the cytokine with the highest differential expression. IL-18 expression was similar in mesothelial cells and the SVF. In both SAT and OAT, IL-18 was immunolocalized in neutrophils and mast cells, but not in macrophages nor adipocytes. This cytokine was also detected in mesothelial cells in OAT. This additional source of expression may explain the higher IL-18 expression levels in OAT than SAT (+5.9-fold). Conclusion: By their capacity to express inflammatory-related factors, and in particular the proinflammatory cytokine IL-18 in OAT, mesothelial cells appear as a new player in the process of low-grade inflammation associated with obesity.